Repeated Sprint Performance and Inter-Limb Asymmetry in Elite Female Sprinters: A Study of Lactate Dynamics and Lower Limb Muscle Activity - Artur Gołaś; Artur Terbalyan; Mariola Gepfert; Robert Roczniok; Aleskander Matusiński; Krzysztof Kotuła; Przemysław Pietraszewski; Adam Zając (Journal of Functional Morphology and Kinesiology, 2025)
Background: Repeated short maximal sprints induce high blood lactate concentrations and may influence neuromuscular coordination, but the relationship between lactate accumulation and inter-limb asymmetry in elite athletes remains unclear. Objectives: This study sought to investigate how blood lactate dynamics during repeated sprint efforts relate to sprint performance and inter-limb muscle asymmetry in elite female sprinters. Methods: Eight elite women (21.3 ± 5.4 y; 54.2 ± 5.1 kg; 165.4 ± 4.3 cm) performed four sets of five all-out 50 m sprints (1 min rest between reps; 5 min between sets). Sprint times were electronically timed. Capillary lactate was measured at rest and 1 min/4 min post-set. Quadricep, hamstring, and gluteal asymmetry was assessed via textile electromyography. Nonparametric statistics (Spearman’s ρ, Friedman test) were applied. Results: From Set 1 to Set 4, sprint time fell from 7.25 ± 0.13 s to 7.07 ± 0.16 s (p = 0.044), 1 min lactate rose from 8.51 ± 2.65 to 15.60 ± 2.66 mmol/L (p < 0.001), and 4 min lactate from 7.16 ± 2.32 to 13.64 ± 2.76 mmol/L (p = 0.002). Muscle group asymmetries decreased (p < 0.01), with lactate at 1 min, correlating negatively with quadriceps (ρ = −0.59) and gluteal (ρ = −0.48) asymmetry. Conclusions: In elite female sprinters, progressive lactate accumulation during repeated 50 m bouts is linked to faster times and reduced muscle asymmetry, suggesting that lactate may enhance neuromuscular coordination under fatigue.